An Emerging Dimension in Psychosomatic Research: The Nocebo Phenomenon in the Management of Chronic Pain. (12th February 2013) - Ciaramella, A.; Paroli, M.; Poli, P.
Abstract : Introduction . The nocebo effect consists in delivering verbal suggestions of negative outcomes so that the subject expects clinical worsening. Several studies indicate that negative verbal suggestions may result in the amplification of pain. Amplification style is one of the most important dimensions in psychosomatic research. Methods . One group of pain therapy unit patients was evaluated at baseline and again after 6 months from the beginning of the pain treatment. Results . Only 43% of 86 chronic pain patients respond positively to the expectation of sham pain. This group shows at baseline higher pain intensity ( t value: 2.72, P = 0.007 ) and lower cold pain threshold ( t value: 2.18, P = 0.03 ) than the group of subjects with any response to sham pain stimulus. Somatoform dimensions influence positively the strength of nocebo response in those predisposed to it. Conclusion . Our study shows that the power of the nocebo phenomenon seems to be a dimension belonging to the investigation in psychosomatic. In contrast to what one might expect, the presence of the nocebo phenomenon affects positively pain relief and the outcome of pain treatment. In a clinical setting, and the meaning of nocebo response does not seem to be different from placebo response.